Maresin 1 Attenuates Lipopolysaccharide-Induced Acute Kidney Injury via Inhibiting NOX4/ROS/NF-κB Pathway - Li, Jiameng; Zhang, Zhuyun; Wang, Liya; Jiang, Luojia; Qin, Zheng; Zhao, Yuliang; Su, Baihai (Frontiers in Pharmacology, 2021)
Sepsis-associated acute kidney injury (S-AKI) is a common complication in hospitalized and critically ill patients, which increases the risk of multiple comorbidities and is associated with extremely high mortality. Maresin 1 (MaR1), a lipid mediator derived from the omega-3 fatty acid docosahexaenoic acid has been reported to protect against inflammation and promote the regression of acute inflammation. This study proposed to systematically investigate the renoprotective effects and potential molecular mechanism of MaR1 in septic acute kidney injury. We established a S-AKI animal model by a single intraperitoneal injection of lipopolysaccharide (LPS), 10 mg/kg, on male C57BL/6J mice. LPS-stimulated (100 μg/ml) mouse kidney tubular epithelium cells (TCMK-1) were used to simulate septic AKI in vitro. The results showed that pretreatment with MaR1 significantly reduced serum creatinine and blood urea nitrogen levels as well as tubular damage scores and injury marker neutrophil gelatinase-associated lipocalin in septic AKI mice. Meanwhile, MaR1 administration obviously diminished pro-inflammatory cytokines (TNF-α, IL-6, IL-1β, and MCP-1), downregulated BAX and cleaved caspase-3 expression, and upregulated BCL-2 expression in the injured kidney tissues and TCMK-1 cells. In addition, MaR1 reduced malondialdehyde production and improved the superoxide dismutase activity of renal tissues while inhibiting reactive oxygen species (ROS) production and protecting the mitochondria. Mechanistically, LPS stimulated the expression of the NOX4/ROS/NF-κB p65 signaling pathway in S-AKI kidneys, while MaR1 effectively suppressed the activation of the corresponding pathway. In conclusion, MaR1 attenuated kidney inflammation, apoptosis, oxidative stress, and mitochondrial dysfunction to protect against LPS-induced septic AKI via inhibiting the NOX4/ROS/NF-κB p65 signaling pathway.